2017
DOI: 10.3390/su9091577
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties of Two Methods in Selecting Priority Areas for Protecting Soil Conservation Service at Regional Scale

Abstract: Soil conservation (SC) is an important ecosystem regulating service. At present, methods for SC mapping to identify priority areas are primarily based on empirical soil erosion models, such as the RUSLE (Revised Universal Soil Loss Equation) based model. However, the parameters of the empirical soil conservation model are based on long-term observations of field experiments at small spatial scales, which are very difficult to obtain and must be simplified when implementing these models at large spatial scales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Therefore, it is a suitable method to estimate the effect of hill slope vegetation rehabilitation on soil conservation. However, this may have been overestimated in this research due to the omission of the local sediment deposition process (Kinnell, 2008) and the use of degraded bare ground as control (Zhang et al, 2017). These overestimations were made for the absolute values of annual SR but did not exclude the SR brought by vegetation rehabilitation.…”
Section: Limitation From Data Sources and Modelsmentioning
confidence: 83%
“…Therefore, it is a suitable method to estimate the effect of hill slope vegetation rehabilitation on soil conservation. However, this may have been overestimated in this research due to the omission of the local sediment deposition process (Kinnell, 2008) and the use of degraded bare ground as control (Zhang et al, 2017). These overestimations were made for the absolute values of annual SR but did not exclude the SR brought by vegetation rehabilitation.…”
Section: Limitation From Data Sources and Modelsmentioning
confidence: 83%
“…However, the increasingly intensification of climate change and human activities can lead to degradation of the FMS, increasingly threatening the local water resources security and ecological stability. In FMS research, flood risk zonation can be executed according to relative risk grade of different areas, Priority Areas for protecting FMS can be designated in local area (Zhang et al, 2017), and some potential problems in regional water crisis could be prevented or mitigated in the future.…”
Section: Implications Of Scenario Analysis For Mapping Fmsmentioning
confidence: 99%
“…Over the past decades, research has shown that the functions and values of ecosystem services have degraded due to climatic and land-use changes [8][9][10]. Recently, the land use and land cover change (LUCC) has been more frequent on the global and regional scales [11,12], and these land conversions may lead to land degradation (e.g., soil erosion, salinization, desertification) [13], biodiversity decline, and the loss of ecosystem services [14,15], which in turn affects food and ecological security. Most studies have suggested that the land-use changes may exert negative impacts on the ESV associated with inappropriate human exploitation [16] and the complex interactions between human and natural drivers of the ESV, rendering the previous studies insufficient for predicting and addressing future problems.…”
Section: Introductionmentioning
confidence: 99%